2021
DOI: 10.25259/sni_240_2021
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID-19 on trainee operative experience at a multihospital academic neurosurgical practice: A first look at case numbers

Abstract: Background: COVID-19 has had a significant impact on the economy, health care, and society as a whole. To prevent the spread of infection, local governments across the United States issued mandatory lockdowns and stay-at-home orders. In the surgical world, elective cases ceased to help “flatten the curve” and prevent the infection from spreading to hospital staff and patients. We explored the effect of the cancellation of these procedures on trainee operative experience at our high-volume, multihospital neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…After removing duplicates, 935 articles were left; their titles and abstracts were screened, and 78 relevant articles were identified for full-text review. Overall, this study collated data and information from 49 articles, [ 11 , 12 , 17 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] ] with 25 of them included in the quantitative synthesis ( Figure 1 ). Twenty-two of these articles were retrospective in nature, two had data collected both retrospectively and prospectively, one was both a retrospective cohort study and a survey.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After removing duplicates, 935 articles were left; their titles and abstracts were screened, and 78 relevant articles were identified for full-text review. Overall, this study collated data and information from 49 articles, [ 11 , 12 , 17 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] ] with 25 of them included in the quantitative synthesis ( Figure 1 ). Twenty-two of these articles were retrospective in nature, two had data collected both retrospectively and prospectively, one was both a retrospective cohort study and a survey.…”
Section: Resultsmentioning
confidence: 99%
“…Majority of the included studies observed a significant decrease in overall caseloads, both surgical and non-surgical, resulting in diminished clinical exposure for residents. [ 12 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [30] , [31] , [32] , [33] , 35 , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] ] Ashry et al found that 56% of the residents had a reduction in their actual role in the surgical steps and the number of residents scrubbing in the same procedure had been decreased to the minimum for preservation of personal protective equipment (PPE). [21] A survey completed by El-Ghandour and colleagues revealed that elective surgery/clinic cancellation occurred more frequently in African countries and that theyr were utilizing PPE significantly less commonly in LMICs (OR=0.441, 95% CI 0.216-0.900, p <0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This increase in research productivity was likely due to the pandemic's limiting effect on clinical practice, particularly elective procedures, of which the U.S. cancelled more than other countries. [27][28][29][30] Studies have demonstrated lower levels of evidence among COVID compared to non-COVID articles. Among the top medical journals, COVID publications were 186-fold more likely to be of lower evidence.…”
Section: Discussionmentioning
confidence: 99%